Quality of Ocimum Gratissimum treated soyabean seeds under different storage conditions - Kwoseh, Charles Kodia (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Philosophy in Plant Pathology,